2011
DOI: 10.1128/aem.05575-11
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Free-Living Protozoa, Cultivable Legionella spp., and Water Quality Characteristics in Three Drinking Water Supplies in the Caribbean

Abstract: The study whose results are presented here aimed at identifying free-living protozoa (FLP) and conditions favoring the growth of these organisms and cultivable Legionella spp. in drinking water supplies in a tropical region. Treated and distributed water (؎30°C) of the water supplies of three Caribbean islands were sampled and investigated with molecular techniques, based on the 18S rRNA gene. The protozoan host Hartmannella vermiformis and cultivable Legionella pneumophila were observed in all three supplies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 58 publications
4
43
1
Order By: Relevance
“…Thus, we next sought to further improve our appreciation of T2S by incorporating a third amoebal host into our analysis. Although hartmannellae and acanthamoebae are the amoebae most frequently implicated as natural hosts for L. pneumophila, studies have implicated Naegleria species as being another natural reservoir (2,53,54). Therefore, we developed a model using N. lovaniensis.…”
Section: U937 Cells (A) H Vermiformis (B) Andmentioning
confidence: 99%
“…Thus, we next sought to further improve our appreciation of T2S by incorporating a third amoebal host into our analysis. Although hartmannellae and acanthamoebae are the amoebae most frequently implicated as natural hosts for L. pneumophila, studies have implicated Naegleria species as being another natural reservoir (2,53,54). Therefore, we developed a model using N. lovaniensis.…”
Section: U937 Cells (A) H Vermiformis (B) Andmentioning
confidence: 99%
“…Modeling of data from a biofilm-batch model indicated that amoebae can only multiply when a threshold concentration of prey bacteria is reached (Kuiper, 2006). Valster et al (2009Valster et al ( , 2011) indicated that the growth of H. vermiformis in drinking water distribution systems is limited at low biofilm concentrations or at ATP concentrations of ≤1 ng L −1 . A number of eukaryotic sequences from the WSW biofilm were related to those of species unlikely to live in biofilm systems, such as Arthropoda and Chordata in Metazoa, and Spermatophyta in Viridiplantae.…”
Section: Eukaryotic Communitiesmentioning
confidence: 99%
“…Compatible with these data, the levels of cas2 mRNA are higher during intracellular growth than during growth in broth (15). The significance of these findings is heightened by the fact that acanthamoebae and hartmannellae are the most common amoebae in waters linked to Legionnaires' disease (6,7,16,17) and cas2 occurs in endemic strains linked to outbreaks (18).The Cas2 family of proteins is best known for being part of the bacterial and archeal clustered regularly interspaced short palindromic repeat (CRISPR)-CRISPR-associated protein (Cas) system, a recently described system that confers immunity against phage and plasmid (19-21). Present in the genomes of nearly all archaea and the genomes of approximately one-half of bacteria, the CRISPR-Cas locus consists of the CRISPR array, which is composed of a variable number of palindromic repeats separated by unique spacer sequences, and a set of cas genes which encodes a variable number of Cas proteins.…”
mentioning
confidence: 99%